1990
DOI: 10.1002/1097-0142(19900801)66:3<597::aid-cncr2820660332>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pseudotumor of Spleen

Abstract: The case of a 66-year-old man with pseudotumor of the spleen is presented. This rare entity can mimic malignant lymphoma clinically and radiographically. Splenectomy is diagnostic and curative. The etiology of pseudolymphoma is unknown, although a review of the literature suggests an association with prior systemic bacterial infection, as in the present case. Cancer 66:597-600,1990.NFLAMMATORY PSEUDOTUMOR (plasma cell granu-I loma) is a rare mass lesion with histologic features of inflammation and mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
4

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 12 publications
0
15
0
4
Order By: Relevance
“…Although inflammatory pseudotumors have been reported in several anatomic locations, 1-8 splenic involvement is extremely rare. Since the first two cases of inflammatory pseudotumor of the spleen were reported by Cotelingam and Jaffe in 1984, 11 24 cases in Japan 12-25 and 42 cases outside Japan 11,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] have been reported. The clinical features of these cases, including the present case, are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inflammatory pseudotumors have been reported in several anatomic locations, 1-8 splenic involvement is extremely rare. Since the first two cases of inflammatory pseudotumor of the spleen were reported by Cotelingam and Jaffe in 1984, 11 24 cases in Japan 12-25 and 42 cases outside Japan 11,14,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] have been reported. The clinical features of these cases, including the present case, are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The granulomatous inflammation process, focal parenchymal necrosis with hemorrhage, disturbance of blood supply, or bacterial or viral infection have all been speculated to be initiators in the spleen. 11,21,29 Perrone et al 38 observed that most of the clinical and pathologic features of inflammatory pseudotumors may thus be related to the production of mediators in inflammation, and noted that interleukin-1 can produce local lesions and systemic manifestations with inflammatory pseudotumors.…”
Section: Discussionmentioning
confidence: 99%
“…8 In splenic inflammatory pseudotumors, the respiratory symptoms of chronic bronchitis and sleep apnea syndrome seen in our case have not been reported previously ; only one case with complications of interstitial pneumonia was reported. 13 Some investigators demonstrated that cytokines such as IL-1b, IL-6, IL-8, and monocyte chemotactic protein-1 were overexpressed in inflammatory pseutotumors. [14][15][16][17] These cytokines are not only associated with the histogenesis of inflammatory pseudotumors but also contribute to clinical manifestations of inflammatory disorders of the lung and sleep-related breathing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations are needed to shed more light on the etiology of this rare tumor. The long-term follow-up of patients with IP showed the benign nature of this lesion [3,16,17,19]. …”
mentioning
confidence: 88%
“…It is more likely an exaggerated hypertrophic scar response to local tissue injury rather than manifestation of a systemic disorder. Splenectomy is diagnostic and curative [5,19]. Further investigations are needed to shed more light on the etiology of this rare tumor.…”
mentioning
confidence: 99%